2016
DOI: 10.1177/0192623315620587
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube and Asbestos Exposures Induce Overlapping but Distinct Profiles of Lung Pathology in Non-Swiss Albino CF-1 Mice

Abstract: Carbon nanotubes (CNTs) are emerging as important occupational and environmental toxicants owing to their increasing prevalence and potential to be inhaled as airborne particles. CNTs are a concern because of their similarities to asbestos, which include fibrous morphology, high aspect ratio, and biopersistence. Limitations in research models have made it difficult to experimentally ascertain the risk of CNT exposures to humans and whether these may lead to lung diseases classically associated with asbestos, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 48 publications
(62 reference statements)
1
15
0
Order By: Relevance
“…One 13-week inhalation study 14) showed that MWCNT exposure induced hyperplasia of epithelial cells after certain observation periods when the concentration of MWCNTs was high. Frank et al (2016) 46) found that the oropharyngeal aspiration of CNT caused alveolar hyperplasia of type 2 pneumocytes at 5 weeks after the end of exposure, although that was not in the bronchoalveolar area, that is the origin of lung cancer. The carcinogenicity of CNTs has been observed in the case of long needle-like structures of CNTs, but If the fiber is shorter, the carcinogenicity of CNTs will be attenuated.…”
Section: ) Discussion and Summary Of The Pulmonary Toxicity Of Cntsmentioning
confidence: 99%
See 1 more Smart Citation
“…One 13-week inhalation study 14) showed that MWCNT exposure induced hyperplasia of epithelial cells after certain observation periods when the concentration of MWCNTs was high. Frank et al (2016) 46) found that the oropharyngeal aspiration of CNT caused alveolar hyperplasia of type 2 pneumocytes at 5 weeks after the end of exposure, although that was not in the bronchoalveolar area, that is the origin of lung cancer. The carcinogenicity of CNTs has been observed in the case of long needle-like structures of CNTs, but If the fiber is shorter, the carcinogenicity of CNTs will be attenuated.…”
Section: ) Discussion and Summary Of The Pulmonary Toxicity Of Cntsmentioning
confidence: 99%
“…Two intratracheal instillation studies of MWCNTs showed lung injury 45,46) . One study using proliferating cell nuclear antigen (PCNA) immunolabeling showed that exposure to pristine or functionalized MWCNTs stimulated the proliferation of alveolar and bronchiolar epithelial cells, although the observation period (16 days) was not long enough to evaluate the persistency of hyperplasia.…”
Section: ) Injury In Respiratory Systemmentioning
confidence: 99%
“…Another study (Wang et al, 2012) documented a decrease in the ability of CNTs to elicit TGF-β in vivo when using a related surfactant (Pluronic F108) as a dispersant. While there has been increasing adoption of BSA/phosphocholine dispersants in CNT aspiration studies, we opted to use Pluronic in this instance in the interest of contiguity with our previously published work (Frank et al, 2015, 2016) using this material. Although we find these dispersion and aspiration methods adequate to illustrate the comparisons captured in the current study, it should be noted that attempts to accurately model human exposures (i.e., for risk analysis) should use true inhalation exposures appropriately adjusted for interspecies differences in respiratory tract dosimetry.…”
Section: Discussionmentioning
confidence: 99%
“…; De Volder et al, 2013). CNTs are high aspect ratio nanofibers which have been experimentally reported to cause chronic inflammation, hyperplasia, and fibrosis of lung tissue (Bonner et al, 2013; Frank et al, 2016; Mercer et al, 2011). Existing literature indicates that CNTs are poorly cleared from the lung in experimental models using inhaled or aspirated exposure doses (Elgrabli et al, 2008; Muller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that CNTs, even in low concentrations, are able to trigger inflammation in the respiratory system of animals [168]. In addition to inflammation, it was revealed that CNTs are also capable of inducing the modulation of proliferation of lung cells as a result of direct injury [169], fibrosis [170], DNA damage [171], and lung cancer [172,173].…”
Section: Toxicity Studies Of Carbon Nanotubesmentioning
confidence: 99%